Implementasi Sirkuit Euler untuk Efisiensi Jalur Kurir pada Layanan Pengiriman Paket - Abdurahman Hamid (PT. Lontara Digitech Indonesia, 2026)
This study aims to analyze the implementation of Euler Circuits in improving the efficiency of courier routes in package delivery services. The study uses a quantitative approach with graph theory methods to model the distribution network into vertices and edges. Vertices represent distribution locations or road intersections, while edges represent connecting paths between locations. The analysis is carried out by determining the degree of each vertex to identify whether the graph meets the requirements as an Eulerian graph. Next, Euler paths are determined using the Fleury and Hierholzer algorithm so that each edge can be traversed exactly once without excessive path repetition. The results show that the implementation of Euler Circuits is able to optimize package distribution routes by reducing the travel distance from 120 km to 90 km. The path efficiency level obtained is 25%. The application of this method has a positive impact in the form of savings in travel distance, reduced distribution time, efficient fuel use, and reduced operational costs. Thus, graph theory, especially Euler Circuits, can be used as an effective mathematical approach in solving path optimization problems in modern logistics and transportation services.